OA37 Secukinumab treatment in children and adolescents with enthesitis-related arthritis and juvenile psoriatic arthritis: efficacy and safety results from a Phase 3 study. (23rd April 2022) - Ramanan, Athimalaipet V; Brunner, Hermine I; Foeldvari, Ivan; Alexeeva, Ekaterina; Ayaz, Nuray A; Calvo, Inmaculada; Kasapcopur, Ozgur; Chasnyk, Vyacheslav G; Hufnagel, Markus; Zuber, Zbigniew; Schulert, Grant; Ozen, Seza; et al.
Abstract: Background/Aims: Enthesitis-related arthritis (ERA) and juvenile psoriatic arthritis (JPsA) are two conditions that represent paediatric correlates of axial spondyloarthritis (axSpA) and adult psoriatic arthritis (PsA), respectively. Secukinumab has demonstrated efficacy and safety in adult patients with PsA, ankylosing spondylitis, and non-radiographic axSpA. This study evaluated efficacy and safety of secukinumab using a randomized, double-blind, placebo-controlled flare prevention design in patients with active ERA and JPsA. Methods: Patients (aged 2 to < 18 years) classified as ERA or JPsA according to ILAR criteria of ≥ 6 months' duration with active disease were included. The 2-year study consisted open-label subcutaneous secukinumab (75/150 mg in patients <50/ ≥50 kg) treatment at baseline, and at Weeks 1, 2, 3, 4, 8, and 12 in treatment period (TP) 1. Responders who achieved at least JIA ACR 30 response at Week 12 were randomized into the double-blind TP2 to continue secukinumab or placebo every 4 weeks until disease flare, or up to Week 100. Primary endpoint was time to flare in TP2; key secondary endpoints included JIA ACR 30/50/70/90/100, inactive disease, juvenile arthritis disease activity score (JADAS), enthesitis and active joint counts, and safety. Analysis of time to flare in TP2 included proportion of patients with disease flare, Kaplan-Meier estimate of median days for time to flare, hazard ratio (HR) estimate, and stratified log-rank test P -value. Intent-to-treat (ITT) analysis using non-responder imputation (NRI) and as-observed analysis were performed for JIA ACR 30/50/70/90/100 responses and inactive disease. Results: 86/97 (88.7%) screened patients were enrolled in TP1 (mean age, 13.1 years; female, 33.7%; ERA, n = 52; JPsA, n = 34) with a mean JADAS-27 score of 15.1 and enthesitis count of 2.6 at baseline. At Week 12, 75/83 (90.4%) patients achieved JIA ACR 30 and entered TP2. There were 21 flares in placebo-treated and 10 flares in secukinumab-treated patients during TP2. Primary endpoint was met: secukinumab-treated patients had significantly longer time to flare versus placebo, resulting in a 72% reduced flare risk (HR: 0.28; 95% CI: 0.13-0.63; P <0.001). There were minor differences between the ITT and as-observed analysis in JIA ACR responses and inactive disease in TP1. Improvement in JADAS-27 score was observed in patients in both ERA and JPsA categories (mean JADAS-27 score of 4.6). Rates of adverse events (AEs; 91.7% vs 92.1%) and serious AEs (14.6% vs 10.5%) in secukinumab and placebo groups were comparable in entire TP. No new safety signals were observed in patients receiving secukinumab (injection-site reaction, n = 1; overall patient-years=141.5). Conclusion: In children and adolescents with ERA and JPsA, efficacy of secukinumab was demonstrated with significantly longer time to flare versus placebo, with sustained improvement of signs and symptoms up to Week 104. Efficacy was observed in ERA and JPsA patients along with a favorable safety profile. Disclosure: A.V. Ramanan: Consultancies; Novartis, Eli Lilly, UCB, Abbvie, Sobi, Roche. Honoraria; Novartis, Eli Lilly, UCB, Abbvie, Sobi, Roche. H.I. Brunner: Consultancies; Aurina, AbbVie, Astra Zeneca-Medimmune, Biogen, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Eli Lilly, EMD Serono, GlaxoSmithKline, F. Hoffmann-La Roche, Merck, Novartis, R-Pharm, Sanofi, Pfizer. Member of speakers' bureau; Pfizer, Roche, GlaxoSmithKline. Grants/research support; Bristol-Myers Squibb, Eli Lilly, GlaxoSmithKline, F. Hoffmann-La Roche, Janssen, Novartis, Pfizer. I. Foeldvari: Consultancies; Novartis, Eli Lilly, Pfizer. E. Alexeeva: Member of speakers' bureau; Novartis, Pfizer, Sanofi, MSD, Amgen, Eli Lilly, Roche. Grants/research support; Novartis, Pfizer, Sanofi, MSD, Amgen, Eli Lilly, Roche. N.A. Ayaz: None. I. Calvo: Consultancies; Sobi, Novartis, Abbvie, GlaxoSmithKline, Pfizer, Amgen, Clementia. Member of speakers' bureau; Sobi, Novartis, Novartis, GlaxoSmithKline, Pfizer, Amgen, Clementia. O. Kasapcopur: None. V.G. Chasnyk: None. M. Hufnagel: Grants/research support; Astellas, F. Hoffmann-La Roche, Novartis. Z. Zuber: None. G. Schulert: Consultancies; Sobi, Novartis. S. Ozen: None. A. Popov: None. C. Scott: None. B. Sözeri: None. E. Zholobova: Member of speakers' bureau; Abbvie, Pfizer, Roche, Novartis. Grants/research support; Pfizer, Novartis. X. Zhu: Other; Employee of Novartis. S. Whelan: Shareholder/stock ownership; Novartis. Other; Employee of Novartis. L. Pricop: Shareholder/stock ownership; Novartis. Other; Employee of Novartis. A. Ravelli: Consultancies; AbbVie, Pfizer. Honoraria; AbbVie, Pfizer, Novartis, Reckitt-Benkiser, Angelini. Member of speakers' bureau; Novartis. Grants/research support; Novartis, Pfizer. A. Martini: Consultancies; Aurinia, Bristol Myers Squibb, Eli-Lilly, EMD Serono, Janssen, Pfizer, Roche. Honoraria; Aurinia, Bristol Myers Squibb, Eli-Lilly, EMD Serono, Janssen, Pfizer, Roche. D.J. Lovell: Consultancies; AstraZeneca, Wyeth, Amgen, Abbott, Pfizer, Hoffmann-La Roche, Novartis, UBC, Janssen, GlaxoSmithKline, Boehringer Ingelheim, Celgene, Bristol Myers Squibb, AbbVie. Member of speakers' bureau; Abbott, Novartis, DSMB member: Forest Research, NIH-NIAMS, Canadian Arthritis Society. N. Ruperto: Honoraria; Ablynx, Amgen, Astrazeneca-Medimmune, Aurinia, Bayer, Bristol Myers and Squibb, Cambridge Healthcare Research (CHR), Celgene, Domain therapeutic, Eli-Lilly, EMD Serono, Glaxo Smith and Kline, Idorsia, Janssen, Novartis, Pfizer, Sobi, UCB.